Chitosan nanoparticles for single and combinatorial delivery of 5-fluorouracil and ursolic acid for hepatocellular carcinoma - Jaiswal, Neha; Pawar, Anil T.; Chaudhari, Bhushan P. (Emergent Materials, 2024)
Hepatocellular carcinoma (HCC) remains a significant global health challenge with limited therapeutic options. Chemotherapy has major limitations, leading to a paradigm shift towards nanomedicines. In this study, we aimed to synthesize single and dual drug-loaded chitosan nanoparticles (CSNPs) containing 5-fluorouracil (5-FU) and ursolic acid (UA) for spatial and controlled delivery against HCC. We synthesized CSNPs by a modified bottom-up ionic gelation method and optimized various parameters to formulate particles with smaller sizes, uniform size distribution, and high surface charge for intra-arterial infusion for HCC. The characterization techniques confirmed a monodisperse population of smaller sized particles with average sizes, as determined from transmission electron microscopy (TEM), as 45.25 ± 11.58, 105.66 ± 10.96, 176 ± 16.46, and 220 ± 21.37 nm for CSNPs, 5-FU-CSNPs, UA-CSNPs and 5FU + UA-CSNPs respectively. These formulations exhibited excellent encapsulation of the drugs, with an initial pH-dependent rapid release of 5-FU followed by a subsequent slower and sustained release, while showing pH-dependent slow and controlled release of UA. The in vitro cell viability assay established the highest anticancer potential for 5FU + UA-CSNPs, followed by 5-FU-CSNPs and UA-CSNPs, and the lowest for plain drugs in the Hep3B cell line. An increased uptake of both the drugs in CSNPs substantiated the supremacy of these formulations over the plain drugs as drug delivery agents. These findings suggest that 5FU + UA-CSNPs, a novel formulation, works as a potent therapeutic agent against HCC, supporting our hypothesis of co-loading 5-FU and UA in CSNPs can effectively manage HCC, with particle attributes fit for administration via intra-arterial infusion.